2021
DOI: 10.3390/f12111485
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Long-Term Light Properties of a Mixed Conifer—Broadleaf Forest in Southwestern Europe

Abstract: Natural and anthropogenic factors affect forest structure worldwide, primarily affecting forest canopy and its light properties. However, not only stand-replacing events modify canopy structure, but disturbances of lower intensity can also have important ecological implications. To study such effects, we analyzed long-term changes in light properties of a conifer–broadleaf mixed forest in the Southwestern Pyrenees, placed in the fringe between the Mediterranean and Eurosiberian biogeographical regions. At this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…1 and 2 ), with Tdir exhibiting the highest spatial distribution heterogeneity. P. massoniana , with its small leaf area, clustered leaves, and high tree height, exhibits low sunlight interception efficiency throughout the year ( Ruiz et al, 2021 ). Moreover, it often forms gaps between adjacent trees ( Messier, Parent & Bergeron, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2 ), with Tdir exhibiting the highest spatial distribution heterogeneity. P. massoniana , with its small leaf area, clustered leaves, and high tree height, exhibits low sunlight interception efficiency throughout the year ( Ruiz et al, 2021 ). Moreover, it often forms gaps between adjacent trees ( Messier, Parent & Bergeron, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 and 4 , Table S1 ). In addition, lower P. massoniana light interception efficiency increases the survival possibilities of other broadleaf tree species in the understory ( Ruiz et al, 2021 ), leading to trees having canopies of varying heights in different seasons, which can effectively absorb and reflect light. As a result, the Tdif fluctuations in the ULE across different seasons were minimal, and its distribution was relatively uniform ( Promis et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition we found that the local distribution of trees and recruits also depended on the patch dynamics, as we found strong differences between plots. In particular, in plots 2, 3, 5 and 9 trees and recruits were aggregated whereas in plot 4 they were repulsed from 1.5 to 6.0 m; the latter spatial patterns was probably due to the local dynamics, such as a strong tree fall as a consequence of a windstorm before the thinning event that created large openings in the local proximity of trees ( Ruiz de la Cuesta et al., 2021 ). We additionally found that recruits in control plots had proportionally higher survival beyond 2.0 m from trees, probably as a consequence of higher tree-recruit competence for resources; for instance, rainfall was proportionally low during the summer season in 2008 and that potentially affected the tree-recruit competence in that year.…”
Section: Discussionmentioning
confidence: 99%